Molecular basis of Thomsen's disease (autosomal dominant myotonia congenita). - George, A; Crackower, M; Abdalla, J; Hudson, A; Ebers, G (1993)
Thomsen's disease (autosomal dominant myotonia congenita) has recently been linked to chromosome 7q35 in the region of the human skeletal muscle chloride channel gene (HUMCLC). Single strand conformation polymorphism analysis (SSCP) was used to screen DNA from members of four unrelated pedigrees with this disorder for mutations in HUMCLC. Abnormal bands were detected in all affected, but no unaffected individuals in three of the families. Direct sequencing revealed a G to A transition that results in the substitution of a glutamic acid for a glycine residue located between the third and fourth predicted membrane spanning segments. This glycine residue is conserved in all known members of this class of chloride channel proteins. These findings establish HUMCLC as the Thomsen's disease gene.